Hemodynamic Results and Mid-term Follow-up of 850 19 to 23 mm Perimount Magna Ease Valves - Anselmi, Amedeo; Ruggieri, Vito Giovanni; Belhaj Soulami, Réda; Flécher, Erwan; Langanay, Thierry; Corbineau, Hervé; Leguerrier, Alain; Verhoye, Jean-Philippe (The Thoracic and Cardiovascular Surgeon, 2019)
Background Aortic valve replacement (AVR) in small aortic roots remains a surgical dilemma with a higher risk of patient-prosthesis mismatch (PPM). The Perimount Magna Ease aortic valve (PMEAV) represents an attractive device in such cases. We examined the early hemodynamic performance, the mid-term outcomes of the PMEAV, and the impact of PPM on outcome and functional class.Methods We performed a retrospective analysis of prospectively collected in-hospital data, and a prospective single-center follow-up of 849 patients who received a 19 to 23 mm PMEAV (2008–2014). Concomitant mitral or tricuspid replacement was the exclusion criterion. Early hemodynamic features were prospectively collected; mid-term follow-up was conducted according to current guidelines.Results Size of implanted prosthesis was 19 mm in 11.5% of patients, 21 mm in 36.9%, and 23 mm in 51.5%. Operative mortality was 4.5% (3.1% for isolated AVR). The rate of severe and moderate PPMs was significantly higher in the 19 mm group. Follow-up was 99.9% complete (3.7 ± 2 years). Actuarial freedom from structural valve deterioration (SVD) at 5 years was 99.1%. At stratified Kaplan–Meier's analysis, PPM and age <70 years were associated with SVD. PPM was not associated with worse functional status (New York Heart Association class) or mortality at follow-up.Conclusion This series shows satisfactory clinical outcomes of the PMEAV implanted in small aortic annuli at mid-term follow-up. Although PPM may occur in smaller sizes, it has limited clinical impact, and it is not associated with mid-term mortality or worse functional class. Few SVD events are evidenced; nonetheless, limited follow-up duration and its methodology need to be considered.
Keywords: aortic valve replacement; patient-prosthesis mismatch; follow-up